Facilitating Agricultural Trade in Asia and the Pacific - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2011)
The Asia-Pacific region is both a major consumer and producer of agricultural products. Its growth in both imports and exports is accelerating, but not to the potential. There is significant opportunity in this region to expand agro-trade especially due to population growth, dietary change of consumers and trade of high-value products. This publication examines a number of constraints that act as barriers to realizing the trade potential of the Asia-Pacific region: cumbersome trade procedures, inadequate compliance to product standards, poor trade logistics and lack of financing for agricultural trade. Some Asia-Pacific countries have adopted effective measures to deal with the problems presented. Still, many countries in this region lag behind in facilitating agricultural trade and will need to adopt similar measures.